Evaluating the long-term survival benefits of high intensity focused ultrasound ablation for hepatocellular carcinoma with portal vein tumor thrombus: a single center retrospective study - Xing Chen; Yuhong Ma; Jun Zhang; Wei Yang; Chengbing Jin; Lifeng Ran; Hui Zhu; Jin Bai; Kun Zhou (International Journal of Hyperthermia, 2022)
Aims To evaluate the long-term survival benefits of high intensity focused ultrasound (HIFU) ablation in patients with hepatocellular carcinoma (HCC) combined with portal vein tumor thrombus (PVTT).Methods The data of patients with HCC-PVTT treated with HIFU from January 2014 to December 2019 were retrospectively analyzed. All patients received HIFU ablation for both PVTT and liver tumor in one session. Perioperative adverse events (AEs) were recorded, and follow-up was performed postoperatively. The Kaplan–Meier method was used for survival analysis.Results Median follow-up was 13.75 ± 1.31 months. A total of 144 patients (male/female: 122/22, age: 54.15 ± 11.84 years old) were included in the study. A total of 267 liver tumors (tumor number: 1.87 ± 1.65, range 1–10) were treated with HIFU. The mean ± SD diameter of viable liver tumors was 100.98 ± 61.65 mm. The reported postoperative AEs of HIFU were skin edema (93.75%), local pain (69.44%) and fever (7.64%). There was no liver failure, gastrointestinal bleeding or perioperative death. The median overall survival (OS) time was 14 months, while the cumulative survival rates of 0.5, 1, 2 and 3 years were 79.0%, 58.6%, 33.3% and 5.9%, respectively. The median OS of PVTT types I, II and III was 22, 13 and 14 months, respectively, and the difference was not statistically significant (p > 0.05).Conclusion HIFU is a minimally invasive method for HCC-PVTT with fewer complications, which could prolong the OS. Patients with PVTT type III could benefit more from HIFU, compared to types I and II.